All sol-gel electrochromic smart windows: CeO2-TiO 2/Ormolyte/WO3 - Avellaneda, C. O.; Dahmouche, K. [UNESP]; Bulhões, L. O. S. (Taylor & Francis Ltd, 2002)
A solid state system having the configuration WO 3/Ormolyte/CeO2-TiO2 has been assembled. Syntheses routes for tungsten oxide WO3, and cerium-titanium CeO 2-TiO2 oxide sols, were developed. A novel solid electrolyte - Ormolyte is reported, which were obtained by the sol-gel process, they have a chemical stability due to the covalent bonds between the inorganic and organic phase, and were prepared with different [O]/[L] ratios, being the best for [O]/[L]=15. The variation of transmittance of the electrochromic device using the ormolyte [O]/[L]=15 was 35% (colored state) and 77% (bleached state).
Keywords: CeO2-TiO2; Ormolyte; Smart windows; WO3; Cerium compounds; Electrochromism; Sol-gels; Solid electrolytes; Titanium dioxide; Tungsten compounds